1932
DOI: 10.1098/rspb.1932.0026
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive processes of certain mammals. III.—The reproductive cycle of the male ferret

Abstract: Cyclic changes in the reproductive organs of male mammals have been studied in a few forms only, but the information available reveals interesting differences in the duration of reproductive activity, and in the correlation between the various organs. Marshall (1911) has described the reproductive cycle in the male hedgehog. Regaud (1904), Tandler and Grosz (1911) and Lecaillon (1909) have studied the mole, but with conflicting results. Rasmussen (1917 and 1918) gives detailed information of the periodic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
2

Year Published

1935
1935
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 4 publications
4
13
2
Order By: Relevance
“…Furthermore, the acrosome of ferret germ cells was positive with the acroleinSchiff reaction of VAN DUIJIN (1961), indicating the presence of proteins. The seasonal histological changes observed in the interstitial cells of the ferret testis are similar to those reported by ALLANSON (1932). They also approximate the changes seen in other feral species, in which the interstitial cells become small and inactive during the sexually quiescent period (squirrel, ALLANSON 1933, MOSSMAN et al 1933, PRASAD 1951, MOSSMAN et al 1955, KIRKPATRICK 1955, MCKEEVER 1963, hedgehog, ALLAN-SON 1934, SCHUTZ 1954, deer, WISLOCKI 1949, wood-mouse, GROOME 1933, mole, LOFTS 1960.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Furthermore, the acrosome of ferret germ cells was positive with the acroleinSchiff reaction of VAN DUIJIN (1961), indicating the presence of proteins. The seasonal histological changes observed in the interstitial cells of the ferret testis are similar to those reported by ALLANSON (1932). They also approximate the changes seen in other feral species, in which the interstitial cells become small and inactive during the sexually quiescent period (squirrel, ALLANSON 1933, MOSSMAN et al 1933, PRASAD 1951, MOSSMAN et al 1955, KIRKPATRICK 1955, MCKEEVER 1963, hedgehog, ALLAN-SON 1934, SCHUTZ 1954, deer, WISLOCKI 1949, wood-mouse, GROOME 1933, mole, LOFTS 1960.…”
Section: Discussionsupporting
confidence: 72%
“…In the present investigation, however, a brown pigment appeared in the interstitial cells of all the degenerating ferret testes. This disagrees with the results of WISLOCKI (1949) and ALLANSON (1932) who reported that this type of pigmentation occurred only in functional testes. The fact that pigmentation was seen only in degenerating testes in the present study suggests that there may be a negative correlation between hormonal activity and pigmentation in these interstitial cells.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The reproductive cycle and the physiological mechanisms controlling seasonal variation in sperma¬ togenesis and circulating testosterone profiles have been characterized in male ferrets (Mustela putoriusfuro) (Allanson, 1932;Baum & Goldfoot, 1974;Walton, 1976;Erskine & Baum, 1982;Sisk & Desjardins, 1986;Kastner & Apfelbach, 1987). Reproductive activity in this species is stimulated by a long-day photoperiod, most breeding occurring from March until August in the northern hemisphere (Neal et ai, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The cyclic histological changes in the testes and in the accessory organs have been described in detail in the ferret ( furo, L.) by Allanson (1932), and in the mole ( Talpaeuropea, L.) by Tandler an and Allanson {unpublished). It was found in both genera that during the breeding season spermatogenesis is complete and very active in the rapidly growing testis, but after that period the reproductive organs return to a quiescent state and sperms are entirely absent.…”
Section: Introductionmentioning
confidence: 99%